2021
DOI: 10.1371/journal.pone.0259435
|View full text |Cite
|
Sign up to set email alerts
|

Using moral foundations in government communication to reduce vaccine hesitancy

Abstract: Having a vaccine available does not necessarily imply that it will be used. Indeed, uptake rates for existing vaccines against infectious diseases have been fluctuating in recent years. Literature suggests that vaccine hesitancy may be grounded in deeply rooted intuitions or values, which can be modelled using Moral Foundations Theory (MFT). We examine the respective prominence of the MFT dimensions in government communication regarding childhood vaccinations and explore its effect on parents’ vaccine hesitanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Discussing the leadership and legitimacy surrounding COVID-19 vaccines may get people's likes. This finding is consistent with a prior study ( Heine & Wolters, 2021 ), which shows that the authority value used in government communication has the largest positive effect on vaccination uptake. The 3 most active sources in mentioning authority value are others, governments, and NGOs.…”
Section: Discussionsupporting
confidence: 93%
“…Discussing the leadership and legitimacy surrounding COVID-19 vaccines may get people's likes. This finding is consistent with a prior study ( Heine & Wolters, 2021 ), which shows that the authority value used in government communication has the largest positive effect on vaccination uptake. The 3 most active sources in mentioning authority value are others, governments, and NGOs.…”
Section: Discussionsupporting
confidence: 93%
“…Across three studies, we hypothesised that higher endorsement of purity and liberty would predict greater reluctance to receive Covid-19 vaccination. These foundations have been identified most often in previous research on moral foundation endorsement and vaccine hesitancy (Amin et al, 2017;Luz et al, 2019;Heine & Wolters, 2021;Nan et al, 2022), though not consistently. We also hypothesised that, though care may not be predictive when considered independently as has been found in some previous studies (Amin et al, 2017;Heine & Wolters, 2021), trade-offs between purity and liberty relative to care would predict greater Covid-19 vaccine reluctance.…”
Section: Discussionmentioning
confidence: 99%
“…A survey of Black Americans found that care and loyalty predicted lower vaccine hesitancy and more favourable attitudes towards the Covid-19 vaccine, while purity and liberty predicted greater hesitancy (Nan et al, 2022). A study looking at the efficacy of emphasising foundations in government communications, found similar null effects for care as Amin et al (2017), with the use of authority and liberty, and to a lesser extent purity, associated with vaccine uptake (Heine & Wolters, 2021). Other research has also linked disgust (an affective purity response) and vaccine reluctance (Luz et al, 2019).…”
Section: Vaccine Attitudes and Moral Foundationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, confidence, complacency, constraints, calculation, and collective responsibility are proposed to underpin vaccine uptake [ 32 ]. Additionally, recent studies of vaccine hesitancy among parents [ 23 , 33 ] and towards the COVID-19 vaccine specifically [ 24 ] have applied social psychological theories of morality to identify the key dimensions of moral judgment and decision-making.…”
Section: Discussionmentioning
confidence: 99%